Analysis of the Effectiveness of E-Wallet Usage in Digital Payment Transactions among Students of University Buana Perjuangan Karawang - Rini Marlita; Uus Mohammad Darul Fadli; Ery Rosmawati (Research in Management of Technology and Business, 2025)
The use of cashless transactions is increasing globally, including in Indonesia. Advances in Internet infrastructure and growing Internet users create significant opportunities for the financial services sector, particularly in digital payments. E-wallets have emerged as the most preferred payment option among students, reflecting changes in financial transaction habits. This study analyses the effectiveness of four leading e-wallets, Gopay, OVO, DANA, and ShopeePay, in meeting students’ transaction needs. The research employs a comparative quantitative approach conducted at Universitas Buana Perjuangan Karawang. The research population comprises 412 2021 Management program cohort students who have used e-wallets. The sample comprises 126 respondents, selected using the Hair et al., (2014) formula, which requires a minimum sample size of five times the total number of questionnaire items. Data were collected through an online Google Forms questionnaire, With measurements conducted using a differential scale ranging from 1 (lowest) to 10 (highest). Data analysis was conducted using validity tests and ANOVA. The results indicate no significant differences in the effectiveness of the four e-wallets. Although there are minor variations in user preferences, their overall effectiveness is relatively equal among Gopay, OVO, DANA, and ShopeePay.